Effect of cimetidine, ranitidine, famotidine and omeprazole on hepatocyte proliferation in vitro - Francavilla, A. (1989)
Recently reports have indicated that both cimetidine and ranitidine delay cell proliferation in rats following 70% partial hepatectomy and result in an increased mortality following this procedure. The present study was designed to determine whether three H(2) blocking agents (cimetidine, ranitidine, famotidine) and a new, powerful antisecretory drug (omeprazole) specifically influence hepatocyte proliferation in primary culture. Hepatocytes were isolated from livers of normal male rats by the standard collagenase perfusion technique. Hepatic DNA synthesis and percent of labelled nuclei were determined after 48 h incubation. Hepatocytes in culture were incubated with the H(2) blocking agents and omeprazole or with different concentrations of serum obtained from sham-operated or 70% hepatectomized rats treated or not with the same agents. Rats were injected intraperitoneally at 8:00 a.m. on two consecutive days. In hepatectomized rats, the first dose was injected at 8:00 a.m. immediately after surgery, the second, 24 h later. The serum of sham-operated or 70% hepatectomized rats that did not receive drugs served as control. No changes in DNA synthesis, percentage of labelled nuclei and transaminase were detected when the agents were added to the hepatocytes in culture at concentrations within the effective pharmacological dosage and 30 times higher. Similarly, no changes in these parameters were obtained when different concentrations of serum obtained from sham-operated rats treated with H(2) blocking agents or omeprazole were added to the basal culture medium. However, a significant inhibition of DNA synthesis and of percentage of labelled nuclei was observed when hepatocytes were incubated in the presence of serum from 70% hepatectomized rats that had been treated with cimetidine or with ranitidine. The serum of 70% hepatectomized rats treated with famotidine and omeprazole had no effect on hepatocyte proliferation in vitro. No effect on transaminase was found in these conditions.